Evaluation of a Microsurgery Training Curriculum - Cuteanu, Anita; Hellich, Agathe; Cardinal, Alba Le; Thomas, Maeve; Valchanova, Anna; Vara, Sital; Horbury, Gwynn; Boal, Matt; Ghamrawi, Walaa; Slim, Naim; Francis, Nader; On behalf of the Microsurgery Training Group at The Griffin Institute (Journal of Reconstructive Microsurgery, 2023)
Background Microsurgery is one of the most challenging areas of surgery with a steep learning curve. To address this educational need, microsurgery curricula have been developed and validated, with the majority focus on technical skills only. The aim of this study was to report on the evaluation of a well-established curriculum using the Kirkpatrick model.Methods A training curriculum was delivered over 5 days between 2017 and 2020 focusing on (1) microscopic field manipulation, (2) knot tying, nondominant hand usage, (3) 3-D models/anastomosis, and (4) tissue experience. The Kirkpatrick model was applied to evaluate the curriculum at four levels: (1) participants' feedback (2) skills development using a validated, objective assessment tool (Global Assessment Score form) and CUSUM charts were constructed to model proficiency gain (3) and (4) assessing skill retention/long-term impact.Results In total, 155 participants undertook the curriculum, totaling 5,425 hours of training. More than 75% of students reported the course as excellent, with the remaining voting for “good.” All participants agreed that the curriculum met expectations and would recommend it. Significant improvement in anastomosis attainment scores between days 1 and 3 (median score 4) and days 4 and 5 (median score 5) (W = 494.5, p = 0.00170). The frequency of errors reduced with successive attempts (chi square = 9.81, p = 0.00174). The steepest learning curve was in anastomosis and patency domains, requiring 11 attempts on average to reach proficiency. In total, 88.5% survey respondents could apply the skills learnt and 76.9% applied the skills learnt within 6 months. Key areas of improvement were identified from this evaluation, and actions to address them were implemented in the following programs.Conclusion Robust evaluation of curriculum can be applied to microsurgery training demonstrating its efficacy in reducing surgical errors with an improvement in overall technical skills that can extend to impact clinical practice. It allows the identification of areas of improvement, driving the refinement of training programs.
Keywords: microsurgery; curriculum; evaluation